Apartheid policy in South Africa - Azi Ayubi (International Journal of Science and Society, 2023)
Racial discrimination is a very big problem and is found in several countries such as the United States, Great Britain and the most dominant in South Africa with the policy of apartheid. Therefore, South Africa is at the center of the fight against racism towards achieving justice. The word apartheid means "separation" in the African language and it describes the racial rigidity that governs the division between the minority white population and the majority white population. The struggle of the majority of black Africans against the domination of white minorities is the main and last racial conflict. The international community actively encourages it. However, the white group was large enough and too strong while the black power was so weak and divided, that in the end a person named Nelson Mandela appeared, who was active in the struggle for the elimination of the politics of apartheid in South Africa on the grounds that racial crises and conflicts would arise. what happened there was soon over and South Africa became an auspicious country.